2008
DOI: 10.1186/1742-4755-5-5
|View full text |Cite
|
Sign up to set email alerts
|

Inter- and intra-observer variability in Sonographic measurements of the cross-sectional diameters and area of the umbilical cord and its vessels during pregnancy

Abstract: Background: The purpose of the study was to evaluate inter-and intra-observer variability in sonographic measurements of the cross-sectional area of the umbilical cord and the diameters of its vessels in low-risk pregnancies of 12 to 40 weeks of gestation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
0
2
0
1
Order By: Relevance
“…In this study, the UCD ranged between 0.73 and 1.68 cm for GAs between 15 and 40 weeks and had a strong positive correlation with GA and EFW (r = 0.679 and r = 0.539, respectively; P < .05). Weissman et al 3 in their study on umbilical cord cross-sectional diameter, for varied GAs, observed that UCD increased progressively, with GA. Other studies [6][7][8] also observed that the UCD increased steadily with GA.…”
Section: Discussionmentioning
confidence: 62%
“…In this study, the UCD ranged between 0.73 and 1.68 cm for GAs between 15 and 40 weeks and had a strong positive correlation with GA and EFW (r = 0.679 and r = 0.539, respectively; P < .05). Weissman et al 3 in their study on umbilical cord cross-sectional diameter, for varied GAs, observed that UCD increased progressively, with GA. Other studies [6][7][8] also observed that the UCD increased steadily with GA.…”
Section: Discussionmentioning
confidence: 62%
“…Gynecologic methods used for measuring the umbilical cord in pregnant women were used for measuring rectal area. 23,24 In the UMNB group, the sensitivity, specificity, positive predictive value and negative predictive value were compared between the rectal diameter and area. The rectal area showed higher values in specificity and positive predictive value compared to the diameter.…”
Section: Discussionmentioning
confidence: 99%
“…Para as medidas do cordão e seus componentes, foi capturada imagem da secção transversa do cordão, adjacente à sua inserção abdominal conforme a técnica utilizada previamente informado sobre a natureza do estudo, mas sem conhecimento das avaliações do examinador anterior, capturava as mesmas medidas de maneira cega. Finalizando, o primeiro examinador fazia nova tomada de medidas, para a avaliação intraobservador (Figura 6) 67 .…”
Section: Avaliação Do Cordão Umbilical E Seus Componentesunclassified